Association of the quality of antenatal care with neonatal mortality: meta-analysis of individual participant data from 60 low- and middle-income countries. Issue 6 (30th May 2019) - Neupane, Subas; Doku, David Teye
Abstract: Background: We investigated the quality of antenatal care (ANC) and its effect on neonatal mortality in 60 low- and middle-income countries (LMICs). Methods: We used pooled comparable cross-sectional surveys from 60 LMICs (n=651 681). Cox proportional hazards multivariable regression models and meta-regression analysis were used to assess the effect of the quality of ANC on the risk of neonatal mortality. Kaplan–Meier survival curves were used to describe the time-to-event patterns of neonatal survival in each region. Results: Pooled estimates from meta-analysis showed a 34% lower risk of neonatal mortality for children of women who were attended to at ANC by skilled personnel. Sufficient ANC advice lowered the risk of neonatal mortality by 20%. Similarly, children of women who had adequate ANC had a 39% lower risk of neonatal mortality. The pooled multivariable model showed an association of neonatal mortality with the ANC quality index (HR 0.85, 95% CI 0.77 to 0.93). Conclusions: Improvement in the quality of ANC can reduce the risk of neonatal mortality substantially. Pursuing sustainable development goal 3, which aims to reduce neonatal mortality to 12 per 1000 live births by 2030, should improve the quality of ANC women receive in LMICs.